2009
DOI: 10.1007/s11064-008-9911-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Granulocyte Colony-stimulating Factor on Intracerebral Hemorrhage in Rat

Abstract: Granulocyte colony-stimulating factor (G-CSF) is a member of the cytokine family of growth factors that can protect the neurons from focal cerebral ischemia-induced injuries. The intracerebral hemorrhage (ICH) has been widely observed in the clinic; however, the protective effect of G-CSF on ICH is still elusive. We found in the present study that the intraperitoneal injection of G-CSF for 5 days could improve the ICH-induced neuronal behavioral impairment measured by limb placement assay. We also observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…A recent study suggested possible contribution of neurogenesis to the beneficial effect of G-CSF against ICH-induced neurological deficits. Indeed, G-CSF treatment increased the number of stem cells in the hemorrhagic region and promoted mobilization of circulating hematopoietic stem cells to the damaged brain areas (64).…”
Section: Growth Factors and Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggested possible contribution of neurogenesis to the beneficial effect of G-CSF against ICH-induced neurological deficits. Indeed, G-CSF treatment increased the number of stem cells in the hemorrhagic region and promoted mobilization of circulating hematopoietic stem cells to the damaged brain areas (64).…”
Section: Growth Factors and Cytokinesmentioning
confidence: 99%
“…On the other hand, prolonged inhibition of Src in the ICH model disturbs repair processes in the neurovascular niche that forms the blood-brain barrier (97), which might worsen long-term outcome. Notably, several drugs including G-CSF (64) and statins (73) have been reported to stimulate neurogenesis in hemorrhagic brain, but contribution of neurogenesis to the effects of these drugs in improving pathological and neurological parameters is unclear at present.…”
Section: Perspectivesmentioning
confidence: 99%
“…On the other hand, growth factors (GF), such as vascular endothelial growth factor (VEGF), angiopoietin 1 (Ang‐1), granulocyte‐colony stimulating factor (G‐CSF), and brain‐derived neurotrophic factor (BDNF), may also play an important role in brain repair after ICH as a result of the stimulation and mobilization of BMPCs recruitment (Asahara et al,1999; Hattori et al,2001; Kermani et al,2005; Engelmann et al,2006; Honold et al,2006; Zhang et al,2009). Likewise, several studies have reported that the chemokine stromal cell‐derived factor‐1α (SDF‐1α) mediates BMPC migration and mobilization in experimental models of stroke (Hill et al,2004; Shyu et al,2008; Wang et al,2008).…”
mentioning
confidence: 99%
“…Because of these properties, G-CSF has been widely used in clinical practice to treat neutropenia induced by chemotherapy, or in the case of BM transplantation (Welte et al, 1996). Recent studies highlighted the efficacy of G-CSF in animal models of cerebral ischemia, reporting significant reduction of infarct size and improved functional recovery (Minnerup et al, 2008;Sevimli et al, 2009;Zhang et al, 2009). The beneficial effects of G-CSF have been attributed to different concurrent mechanisms, including antiapoptotic activity (Schäbitz et al, 2003;Schneider et al, 2005), immunomodulation (von Aulock et al, 2004), stimulation of neurogenesis (Schneider et al, 2005;Kawada et al, 2006;Diederich et al, 2009), and angiogenesis (Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%